Pengembangan Lembar Kerja Peserta Didik Digital Interaktif Berbasis Higher Order Thinking Skills Untuk Pembelajaran Matematika di Sekolah Dasar - Indhira Asih Vivi Yandari; Aulia Dinayah; Aan Subhan Pamungkas; Sigit Setiawan (SJME (Supremum Journal of Mathematics Education), 2023)
The background of this development is the importance of higher order thinking skills for primary school students, to support these abilities, it is necessary to have learning resources that support and are in accordance with technological developments. However, the facts in the school show that existing learning resources are still conventional and have yet to lead to the achievement of higher order thinking. Based on this background, the purpose of this development is to develop HOTS-based digital student worksheets in mathematics learning in primary schools. This research was conducted at SDIT Al-Hujjaj Cilegon City for fifth grade students. The development model used is the ADDIE model, namely Analysis, Design, Development, Implementation, Evaluation. The instruments used to measure the feasibility of this products are expert validation questionnaires consisting of media experts, content experts, and language experts, practicality questionnaires and higher order thinking skills tests. Based on the results of processing the expert validation questionnaire, the results obtained are the media expert's assessment getting an average percentage score of 88% with very feasible criteria, the content expert's assessment getting an average percentage score of 91% with very feasible criteria, and the linguist's assessment getting an average percentage score of 90% with very feasible criteria. The results of processing the practicality questionnaire distributed to teachers and students received a percentage score of 95.2% with very practical criteria. While the test results show the achievement score of students' higher-level thinking skills of 93.8% with very good criteria and above the minimum completeness criteria set at 70. Based on the results of the analysis, it can be concluded that the student worksheets developed are feasible and practical to use as complementary teaching materials and effective in developing students' critical thinking skills in mathematics learning in primary schools.